The Metaverse Applied to Education: Systematic Review of Scientific Knowledge Published in Spain - Conde Melguizo, Rafael; Serrano Archila, Jorge; Blázquez Piñeiro, Fernando José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The metaverse is a concept that has gained popularity in the last decade, especially after the conversion of the Facebook company to Meta. In this article, a systematic review of the scientific literature in Spain related to the metaverse applied to education is carried out. In general, a low scientific quality has been observed in a significant part of the publications, especially with a lack of information about the methodology or the sample used in the studies. This review suggests a need to improve the quantity and quality of research about metaverse and education in Spain in the coming years.